Implementasi Akad Ba’I Al Muqayyadah Dalam Menigkatkan Kepercayaan Konsumen Pada Transaksi Tukar Tambah HP Bekas - Moh. Fakhri Siddiqi; Saifuddin; Makkiyatul Umaroh (ITB AAS INDONESIA Surakarta, 2025)
This study discusses the implementation of the Bai' al-Muqayyadah contract in used cellphone exchange transactions at the Difa Cell Besuk counter. This contract is used to ensure that transactions run according to sharia principles, such as justice, honesty, and transparency, and avoid elements of usury and gharar. This study aims to analyze the mechanism for assessing cellphone conditions, the negotiation process, applicable laws, and the challenges faced in implementing this sharia contract. The approach used is qualitative with a case study method. Data were obtained through direct observation, interviews with related parties, and document analysis. The results of the study are expected to provide guidance for business actors and consumers in conducting used cellphone exchanges in an Islamic and economical manner, as well as contributing to Islamic economic literature related to the implementation of sharia contracts in daily transactions.